2009
DOI: 10.1016/j.jnucmat.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Zircaloy cladding hulls from spent nuclear fuel

Abstract: The feasibility of decontaminating spent fuel cladding hulls using hydrofluoric acid (HF) was investigated as part of the Global Energy Nuclear Partnership (GNEP) Separations Campaign. The concentrations of the fission product and transuranic (TRU) isotopes in the decontaminated hulls were compared to the limits for determining the low level waste (LLW) classification in the United States (US). The 90 Sr and 137 Cs concentrations met the disposal criteria for a Class C LLW; although, in a number of experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The importance of the cladding hull waste cannot be underestimated owing to its large portion (about 25% of nuclear material) and high radioactivity. Previous works suggest that cladding hull waste should be treated as a GTCC (Greater Than Class C) or HLW (high level waste) [1,2]. In the case of pyro-processing, which employs electrochemical reactions to recover nuclear materials from the SNF, the cladding hulls are separated from nuclear materials using an oxidative decladding process [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the cladding hull waste cannot be underestimated owing to its large portion (about 25% of nuclear material) and high radioactivity. Previous works suggest that cladding hull waste should be treated as a GTCC (Greater Than Class C) or HLW (high level waste) [1,2]. In the case of pyro-processing, which employs electrochemical reactions to recover nuclear materials from the SNF, the cladding hulls are separated from nuclear materials using an oxidative decladding process [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Even after the oxidative decladding, a little amount of SNF stuck on the inner surface of the hulls cannot be removed completely. In addition, some of the fission products penetrate into the hulls [2] and the radioactivation of the hulls also produces various radioactive nuclides inside the hulls [7]. These various impurities make it difficult to decontaminate the cladding hull waste to treat it as an intermediate-or low-level waste.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, acid washing and compaction techniques are widely employed to manage the cladding hull waste. The acid washing is a convenient method to remove residual UNF from the cladding hulls that are stuck on the inner surface, but it is also well known that the acid washing procedure is insufficient to classify the cladding hull waste as a low-level waste [3,4]. In addition, it was revealed that the radioactivity of 94 Nb, which is one of the major radioactivation products of Nb contained in ZIR-LO (ZIRconium Low Oxidation) cladding hull material, exceeds acceptance limit of the Wolsong LILW (Low and Intermediate Level Waste) disposal center (WLDC) of Korea [5].…”
Section: Introductionmentioning
confidence: 99%
“…The SNF consists of fuel material (fissionable material and fission products), cladding hull, and hardware waste, and the mass ratio of each component is about 100: 25: 5.7 [5]. It was also reported that the cladding hull waste generated during the wet reprocessing of SNF should be treated as Greater Than Class C (GTCC) waste or High Level Waste (HLW) [5,6]. In the case of the pyroprocess, it was suggested that the hull wastes generated during the pyroprocess needs further treatment to be recycled or disposed of as low level waste, owing to the residual SNF stuck on the inner surface of the hulls, the fission products (FPs) penetrated into the hulls, and the radioactivation of cladding hull constituents [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the cladding hull waste generated during the wet reprocessing of SNF should be treated as Greater Than Class C (GTCC) waste or High Level Waste (HLW) [5,6]. In the case of the pyroprocess, it was suggested that the hull wastes generated during the pyroprocess needs further treatment to be recycled or disposed of as low level waste, owing to the residual SNF stuck on the inner surface of the hulls, the fission products (FPs) penetrated into the hulls, and the radioactivation of cladding hull constituents [6][7][8]. To minimize the amount of HLW generated during the pyroprocess, KAERI is developing a chlorination technique as a hull waste treatment method [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%